Associations of symptoms and quality of life with outcomes in patients with atrial fibrillation. Issue 23 (31st March 2020) - Krisai, Philipp; Blum, Steffen; Aeschbacher, Stefanie; Beer, Jürg H; Moschovitis, Giorgio; Witassek, Fabienne; Kobza, Richard; Rodondi, Nicolas; Moutzouri, Elisavet; Mahmood, Aamina; Healey, Jeff S; Zuern, Christine S; et al.
Abstract : Objective: We aimed to investigate changes in atrial fibrillation (AF)-related symptoms and quality of life (QoL) over time, and their impact on prognosis. Methods: We prospectively followed 3836 patients with known AF for a mean of 3.7 years. Information on AF-related symptoms and QoL was obtained yearly. The primary end point was a composite of stroke or systemic embolism. Main secondary end points included stroke subtypes, all-cause mortality, cardiovascular death, hospitalisation for congestive heart failure (CHF), myocardial infarction and major bleeding. We assessed associations using multivariable, time-updated Cox proportional hazards models. Results: Mean age was 72 years, 72% were male. Patients with AF-related symptoms (66%) were younger (70 vs 74 years, p<0.0001), more often had paroxysmal AF (56% vs 37%, p<0.0001) and had lower QoL (71 vs 72 points, p=0.009). The incidence of the primary end point was 1.05 and 1.02 per 100 person-years in patients with and without symptoms, respectively. The multivariable adjusted HR (aHR) (95% CIs) for the primary end point was 1.11 (0.77 to 1.59; p=0.56) for AF-related symptoms. AF-related symptoms were not associated with any of the secondary end points. QoL was not significantly related to the primary end point (aHR per 5-point increase 0.98 (0.94 to 1.03; p=0.37)), but was significantly related to CHF hospitalisations (0.92 (0.90 to 0.94; p<0.0001)), cardiovascular death (0.90 (0.86 to 0.95; p<0.0001)) and all-cause mortality (0.88 (0.86 to 0.90; p<0.0001)). Conclusions: AF-related symptoms were not associated with adverse outcomes and should therefore not be the basis for prognostic treatment decisions. QoL was strongly associated with CHF, cardiovascular death and all-cause mortality.